What is the relationship between Learning Design and TPACK? - Campbell, C.; Dobozy, Eva (IEEE Computer Society, 2013)
There is a great deal of literature currently available on eLearning and there are numerous available models on integrating technology into teaching practices, in the areas of mobile learning and blended learning. This paper will investigate two areas that are emerging as leaders in the field; namely Learning Design and Technological, Pedagogical and Content Knowledge, which is also referred to as TPACK. By exploring these two areas it is possible to interpret where the two areas intersect and to move the literature forward on both areas. Learning Design is a sub-field of eLearning, while TPACK has gained a great deal of currency after being developed by Misher and Koehler (2006) earlier this century. This paper demonstrates that by using these two frameworks together it allows for a stronger epistemological foundation and better design for teaching. © 2013 IEEE.